Failing Our Veterans : The G.I. Bill and the Vietnam Generation - Boulton, Mark, 1973- (Book collections on Project MUSE., 2014)
The original 1944 G.I. Bill holds a special place in the American imagination. In popular mythology, it stands as the capstone of the Greatest Generation narrative of World War II, a fitting reward for the nation's heroes. Given the almost universal acclaim afforded the bill, future generations of warriors might well have expected to receive similar remuneration for their sacrifice. But when soldiers of the Vietnam conflict shed their fatigues and returned home to civilian life, they found that their G.I. Bills fell well short of what many of them believed they had earned. In this first legisl.